2003
DOI: 10.1002/jsfa.1299
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing treatments on the characteristics of juices and still ciders from Ontario‐grown apples

Abstract: Recent interest in the commercial production of cider in Ontario, Canada revealed a lack of information on cider prepared from apples grown in North America. A study was conducted using locally grown culinary and dessert varieties of apples, since there is a lack of true cider varieties grown in Ontario. Four processing methods (treatments) were evaluated with respect to their effect on juice and cider characteristics; the chemical and microbiological characteristics of the juices and still ciders are reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…patuline , minimising problems in terms of dessert apple production . The literature includes reports regarding dessert varieties used for cider making, including Fuji apples , Ralls , Lietuvas Pepins, Auksis, Remo, Merry Gold and others , Crispin and McIntosh and Šampion, Idared and Gloster .…”
Section: Introductionmentioning
confidence: 99%
“…patuline , minimising problems in terms of dessert apple production . The literature includes reports regarding dessert varieties used for cider making, including Fuji apples , Ralls , Lietuvas Pepins, Auksis, Remo, Merry Gold and others , Crispin and McIntosh and Šampion, Idared and Gloster .…”
Section: Introductionmentioning
confidence: 99%
“…The formation of higher alcohols is temperature dependent, so that changes in temperature may cause changes in the availability of fusel alcohols that are necessary for ester formation (Calderbank and Hammond ). To our knowledge, for apple wine, the parameters that have been studied for their influence on major volatile compounds are mainly focused on yeast types, SO 2 dosage, initial nitrogen content, aging time, juice processing methods, and so on (Leguerinel and others ; Herrero and others ; Wilson and others ; Choi and Nielsen ; Valles and others ; Peng and others ; Kelkar and Dolan ), and the effects of fermentation temperature on the concentration of aromatic compounds and sensory properties of apple wine have been less studied (Herrero and others ).Therefore, it is very important to understand the effects of fermentation temperature on volatile aroma compounds, especially the key compounds that could have a great aromatic impact on apple wines, for improving both the processing technique and final product quality.…”
Section: Introductionmentioning
confidence: 99%
“…The Fuji juice presented a higher amount of soluble solids, and the content of fructose in both samples was similar (around 69%). Wilson et al [31] found a fructose content of about 50% in apple juices from five different varieties harvested in Canada. These values are related to different stages of maturity, harvest, and place of production of apples.…”
Section: Resultsmentioning
confidence: 99%
“…Wilson et al. found a fructose content of about 50% in apple juices from five different varieties harvested in Canada. These values are related to different stages of maturity, harvest, and place of production of apples.…”
Section: Resultsmentioning
confidence: 99%